MENINGKATKAN PERAN KELUARGA DALAM TANGGAP DARURAT BENCANA PANDEMIK COVID-19 - Sriwulan Megawati; Iman Abidin; Iceu Mulyati; Manaf Bin Saman; Nur Intan Hayati Husnul Khotimah (Abdimas Siliwangi, 2021)
The discovery of positive confirmed cases of Covid-19 in the Cibiru Asri I complex area has an impact on residents in that environment, such as panic, worries about Covid-19 transmission, increased stress and fatigue, while knowledge about prevention measures for transmission in public places is still not optimal, marked by the use of masks which is not appropriate, hand washing facilities are not yet available and knowledge about stress management is inadequate, even though this can reduce immunity and the risk of Covid 19 transmission occurs. This activity aims to increase the role of families, especially mothers in responding to the Covid-19 outbreak. The method used as a solution to overcome partner problems is by holding educational activities about the Covid-19 disease; self-assessment of Covid-19 in families (selfi), hand washing movements (harewos), movements of wearing masks, making hand sanitizers and disinfectants (hade), healthy liver movements (hearts), stress management with finger handheld therapy and donations made online and offline. Based on the evaluation, it was found that almost all of the mothers (80%) who participated in educational activities about Covid-19, self-assessment, hand washing movements and wearing masks were in the good category, while the stress levels of mothers after being given finger handheld therapy were almost entirely (73, 3%) are in the normal category. This shows that community service activities in the form of education provided by the community service team can increase mothers' knowledge of preparedness to face Covid-19. Education for mothers can increase family knowledge, because mothers are people who act as protectors of the family, especially their children. So that education by involving mothers is necessary to continue to increase the independence of the family in facing disasters.Keywords: Covid-19, Emergency Response, Family Role